The Influence of Learning Strategies and Learning Motivation on the Learning Outcomes of PAI Students at SMPN 2 Telukjambe Timur Karawang - Nurhasan; Muhamad Faizin; Abdul Kosim; Saprialman; Neni Yunia; Chatur Wassesa; Ana Tiara Syalwa (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this research is to determine how students taught with inquiry-based learning strategies differ from students taught with expository-based learning strategies in terms of their PAI learning outcomes, how students taught with inquiry-based and expository-based learning strategies differ in terms of their overall learning motivation, and how learning strategies and learning motivation interact to affect PAI learning outcomes. different in terms of overall learning motivation, and how learning strategies and learning motivation interact to affect PAI learning outcomes. With PAI learning outcomes as the dependent variable, the treatment of learning strategies as the independent variable, and the quality of learning motivation as the independent variable, this research was conducted using an experimental methodology. By incorporating certain learning motives, the 2x2 factorial experimental design compares two learning strategies: the expository learning approach and the inquiry learning strategy. The results of this study indicate that the average PAI learning outcomes of students taught using the inquiry learning strategy ( = 83.08) are higher compared to the average PAI learning outcomes of students taught using the expository learning strategy ( = 78.87). This is also evidenced by the significance value = 0.024 < α = 0.05. The average PAI learning outcomes of students with high learning motivation ( = 83.45) overall, whether taught with inquiry learning strategies or expository learning strategies, are higher compared to the average PAI learning outcomes of students with low learning motivation ( = 79.26). This is also evidenced by the significance value = 0.028 < α = 0.05. And there is an interaction between learning strategies and student learning motivation that has a different impact on PAI learning outcomes. This is evidenced by the significance value = 0.009 < α = 0.05.